PENERAPAN LOGIKA BOOLEAN DALAM PROGRAM PERMINTAAN BARANG BERBASIS WEB - Prayogo Prayogo; Mochammad Fauzi (Universitas PGRI Adi Buana Surabaya, 2015)
This research is motivated by the fact that math is less desirable by students. This is due to lack of knowledge of the teachers in implementing the learning by using the methods in the abstract explanation. Then, the students only know how to calculate the numbers and not fully understood about the use of mathematical material itself. This research aims to provide information for the teachers in order to better understand the usefulness of mathematics material. Then the teacher is able to show the function of mathematics, especially mathematical logic, and the theacher will further enhance student’s motivation in learning mathematics. The research method used in this research is the study of literature, namely by reviewing, researching and investigating and studying the scientific works presented in the form of books, paper, or papers that are relevant to the research topic. Then the results are translated and rearranged in detail into a paper. Keywords : implementation, logic, boolean programs, web